2012
DOI: 10.1095/biolreprod.111.093864
|View full text |Cite
|
Sign up to set email alerts
|

Role of FYN Kinase in Spermatogenesis: Defects Characteristic of Fyn-Null Sperm in Mice1

Abstract: FYN kinase is highly expressed in the testis and has been implicated in testis and sperm function, yet specific roles for this kinase in testis somatic and germ cells have not been defined. The purpose of the present investigation was to identify aspects of spermatogenesis, spermiation, or sperm fertilizing capacity that required FYN for normal reproductive function. Matings between Fyn-null males and wild-type females resulted in normal litter sizes, despite the fact that Fyn-null males exhibited reduced epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
0
17
0
1
Order By: Relevance
“…The use of a secondary antibody that specifically detects native IgGs avoided detection of denatured IgGs used for immunoprecipitation (see "Experimental Procedures"). Regarding the presence of other SFK members in mouse sperm, Fyn has been reported recently (21) to have an active role in spermatogenesis. To analyze the possible activation of Fyn during capacitation, the anti Tyr-416-Src was used because it cross-reacts with all members of the SFK family when phosphorylated at the analogous site (Tyr-420-Fyn).…”
Section: Inhibition Of Csrc Does Not Affect Phosphorylation Cascadesmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a secondary antibody that specifically detects native IgGs avoided detection of denatured IgGs used for immunoprecipitation (see "Experimental Procedures"). Regarding the presence of other SFK members in mouse sperm, Fyn has been reported recently (21) to have an active role in spermatogenesis. To analyze the possible activation of Fyn during capacitation, the anti Tyr-416-Src was used because it cross-reacts with all members of the SFK family when phosphorylated at the analogous site (Tyr-420-Fyn).…”
Section: Inhibition Of Csrc Does Not Affect Phosphorylation Cascadesmentioning
confidence: 99%
“…Work from several laboratories has shown the presence of members of the Src family of kinases (SFK), in mouse sperm: cSrc (3,11,12) Fyn (13), and immunocytochemistry-based evidence on Lyn and Hck (11). However, recent work from our group using a combination of pharmacological and genetic approaches has shown that, although SFK inhibitors affect phosphorylation by up-regulation of Ser/Thr phosphatases, SFKs are not directly involved in the increase in tyrosine phosphorylation observed during sperm capacitation that follows PKA activation.…”
mentioning
confidence: 99%
“…The phosphorylation of proteins is mediated by the activity of kinases that are present in spermatozoa including those of the MAP kinase pathway [ 15 -17 ], CaMKII alpha [ 18 ], FYN kinase [ 19 ], JAK/STAT [ 20 ] and many others. Most of these kinases have been studied from the standpoint of their roles in sperm capacitation and fertilization, and will not be addressed here.…”
Section: Phosphorylationmentioning
confidence: 99%
“…A list of potential candidate kinases has emerged based on pharmacological and immunological evidence. Among these candidates, the most relevant were SRC (Baker et al, 2006;Krapf et al, 2010;Varano et al, 2008), FYN (Luo et al, 2012), ABL (Baker et al, 2009), and both members of the focal adhesion kinase (FAK) family, FAK and proline-rich tyrosine kinase 2 (PYK2; also known as PTK2B) (Battistone et al, 2014;Gonzalez-Fernandez et al, 2013). All these enzymes were shown to be present in sperm and, furthermore, the increase in tyrosine phosphorylation was reduced or completely obliterated when treated with inhibitors against their respective activities.…”
Section: Introductionmentioning
confidence: 99%